THE EFFECT OF AUDIO-VISUAL MEDIA ON VOCABULARY RETENTION OF THE 9th GRADE STUDENTS AT AN ISLAMIC BOARDING SCHOOL IN LOMBOK, INDONESIA - Silvia Eka Safitri; Santi Farmasari; Lalu Thohir (Program Studi Pendidikan Bahasa Inggris, 2022)
This study focuses on investigating the effect of audio-visual media (AVM) on students’ vocabulary retention and determining students’ perception about learning using AVM. This experimental research was conducted at an Islamic Boarding School in West Lombok Indonesia. The population of the study were the 9th grade students. Two classes were selected using cluster random sampling method. Each class consists of twenty-eight students, 56 in total. The classes were divided into two groups; Experimental and Control group. Pre-Test and Post-Test design and Survey method were used in the data collection. The data indicate that there was no student in the experimental group classified into excellent category, but after doing the treatment the students’ scores in the experimental group improved well. The result of paired sample test showed the Sig. value was 0.00 < 0.05 which means there was a significant difference of students’ learning outcome.